Asuhan Kebidanan Berkelanjutan Ny. “H” Di Rumah Sakit Khusus Daerah Ibu Dan Anak Siti Fatimah Makassar Tahun 2023 - Husnul Hatima; Endang Sulistyowati (Jurnal Ventilator, 2024)
Mother and Child Health (MCH) requires efforts through a holistic approach known as Continuity of Care (COC). Continuity is essential throughout a woman's life cycle, including during pregnancy, childbirth, and the postpartum period. To achieve COC, it can be implemented through monitoring and services such as ANC, INC, PNC, and Newborn Care, as well as connecting healthcare facilities to ensure prompt and accurate handling of emergencies. The aim of this research is to provide comprehensive midwifery care for pregnant women in the third trimester, during labor, postpartum, care for the newborn, neonates, and family planning. The study was conducted from April to May 2023 at the Special Regional Hospital for Mother and Child, Siti Fatima, Makassar. The care method in this research involves interviews, observations, and management of the subject's care. The subject in this care is Mrs. "H," a woman in her second pregnancy, who has given birth once, is currently at 37 weeks and 4 days gestation. The results of comprehensive midwifery care for Mrs. "H" during the third trimester of pregnancy showed well-preparedness for childbirth. Normal delivery occurred, followed by normal care for the newborn and neonatal care. The conclusion of this research is that comprehensive care allows for data collection, determination of actual and potential diagnoses, and timely referral or collaboration with other healthcare providers in case of issues.